2018
DOI: 10.1371/journal.pone.0193240
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional intra-amniotic therapy increases survival in a rabbit model of fetal growth restriction

Abstract: ObjectiveTo evaluate the perinatal effects of a prenatal therapy based on intra-amniotic nutritional supplementation in a rabbit model of intrauterine growth restriction (IUGR).MethodsIUGR was surgically induced in pregnant rabbits at gestational day 25 by ligating 40–50% of uteroplacental vessels of each gestational sac. At the same time, modified-parenteral nutrition solution (containing glucose, amino acids and electrolytes) was injected into the amniotic sac of nearly half of the IUGR fetuses (IUGR-T group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 39 publications
0
18
0
1
Order By: Relevance
“…Lactoferrin supplementation also improved brain hippocampal structure and stimulated brain derived neurotrophic factor (BDNF) (197), important observations in light of the neuropathology associated with human FGR. Nutritional supplementation (glucose, amino acids and electrolytes) into the amniotic sac of FGR rabbits has also recently been explored, with some promising results suggesting that survival rate for FGR offspring was improved with treatment, although birth weight and cardiac function deficits were not improved (198).…”
Section: Specific Neonatal Morbidities (Table 1)mentioning
confidence: 99%
“…Lactoferrin supplementation also improved brain hippocampal structure and stimulated brain derived neurotrophic factor (BDNF) (197), important observations in light of the neuropathology associated with human FGR. Nutritional supplementation (glucose, amino acids and electrolytes) into the amniotic sac of FGR rabbits has also recently been explored, with some promising results suggesting that survival rate for FGR offspring was improved with treatment, although birth weight and cardiac function deficits were not improved (198).…”
Section: Specific Neonatal Morbidities (Table 1)mentioning
confidence: 99%
“…There were also changes in the heart and kidneys in rabbit kits in response to surgical ligature of uteroplacental vessels. In particular, reduced uteroplacental blood flow decreased fetal heart weight and caused systolic and diastolic dysfunction (Schipke et al, ) in association with an increase in myocardial wall thickness, left ventricular hypovascularisation and hypertrophy, altered expression of metabolic genes, and disorganized cardiomyocyte ultrastructure (reduced sarcomere length and mitochondrial density; Gonzalez‐Tendero et al, ; Guitart‐Mampel et al, ; Gumus et al, ; Schipke et al, ; Torre et al, ). Utero‐placental insufficiency also reduced kidney weight, decreased renal glomeruli number and lead to glomerular capillary congestion and oxidative stress in developing rabbits kits (Bassan et al, ; Figueroa et al, ).…”
Section: Models Of Iugr and Fetal Programmingmentioning
confidence: 99%
“…Similarly, several studies also demonstrated programming effects of prenatal hypoxia in the mammalian hearts of IUH rodent model offspring [43, 55, 56]. It is important to mention that a number of studies reported that maternal dietary supplementation with Arg, a major substrate of PA production, increases BW and decreases perinatal mortality in rat, ewe, and rabbit models exposed to IUGR during the gestation period [22, 57, 58]. Moreover, supplementation with Arg was sufficient to increase SPD concentrations in colonic tissue and blood [59, 60].…”
Section: Discussionmentioning
confidence: 99%